Uso do acesso lateral para aspiração folicular em ovelhas Santa Inês - Mariano, Renata Sitta Gomes [UNESP] (2015)
The laparoscopic ovum pick-up is widely used in reproductive biotechnology, although there are physiological changes in the cardiorespiratory system due to Trendelenburg position. For this reason and in order to decrease these events we developed a new surgical approach in the lateral position for follicular aspiration. 24 Santa Ines sheep randomly divided into two groups with 12 animals: GL - positioned in right lateral position and head down position of 10 degree; GD - supine positioned and an head down inclination of 35 degree. The animals were submitted to laparoscopic ovum pick-up procedure, using three portals and CO2 pneumoperitoneum. The surgery times, visualized and aspirated follicles, oocytes recovery, heart and respiratory rate, mean arterial pressure, pressure at the end of the exhaled CO2, post surgery analgesia and serum fibrinogenic were evaluated before, during and after surgery. The total surgery time, heart rate, mean arterial pressure, and EtCO2 were higher in the GL. While visualized and aspirated follicles, recovery oocytes, fibrinogen, respiratory rate and post surgery analgesia were similar between groups. The follicular aspiration technique for lateral approach presents as viable and effective procedure for oocytes recovery in Santa Ines sheep. However, it is important to mention that this approach requires considerable changes in cardiorespiratory system compared to the conventional approach, making their practical applicability limited